A structurally distinct TGF-β mimic from an intestinal helminth parasite potently induces regulatory T cells. Issue 1 (December 2017) - Johnston, Chris; Smyth, Danielle; Kodali, Ravindra; White, Madeleine; Harcus, Yvonne; Filbey, Kara; Hewitson, James; Hinck, Cynthia; Ivens, Alasdair; Kemter, Andrea; Kildemoes, Anna; Bihan, Thierry; et al.
Abstract Helminth parasites defy immune exclusion through sophisticated evasion mechanisms, including activation of host immunosuppressive regulatory T (Treg) cells. The mouse parasiteHeligmosomoides polygyrus can expand the host Treg population by secreting products that activate TGF-β signalling, but the identity of the active molecule is unknown. Here we identify anH. polygyrus TGF-β mimic (Hp- TGM) that replicates the biological and functional properties of TGF-β, including binding to mammalian TGF-β receptors and inducing mouse and human Foxp3+ Treg cells.Hp- TGM has no homology with mammalian TGF-β or other members of the TGF-β family, but is a member of the complement control protein superfamily. Thus, our data indicate that through convergent evolution, the parasite has acquired a protein with cytokine-like function that is able to exploit an endogenous pathway of immunoregulation in the host. Heligmosomoides polygyrus can activate mammalian TGF-β signalling pathways, but how it does so is not known. Here the authors identify and isolate aH. polygyrus TFG-β mimic that can bind both mammalian TGF-β receptor subunits, activate Smad signalling and generate inducible regulatory T cells.